Effect of TiC and NbC carbides on creep life of stainless steels. (2nd January 2019) - Abe, F.; Murata, M.; Miyazaki, H.
Abstract: The effect of TiC and NbC carbides on creep life has been investigated for 321HTB and 347HTB steels at 600–750°C for about 20–200, 000 h. The creep data for 304HTB steel are used as reference data. The precipitation hardening is larger for the 321HTB than for the 347HTB at short times during creep. Then the reduction of precipitation hardening due to coarsening of TiC and NbC carbides takes place for up to long times, which is less significant in the 321HTB than in the 347HTB. The smaller coarsening rate of the TiC carbides than the NbC carbides during creep is discussed on the base of a rate equation for diffusion-controlled Ostwald ripening.